2016
DOI: 10.1158/1535-7163.mct-16-0211
|View full text |Cite
|
Sign up to set email alerts
|

FLIP: A Targetable Mediator of Resistance to Radiation in Non–Small Cell Lung Cancer

Abstract: Resistance to radiotherapy due to insufficient cancer cell death is a significant cause of treatment failure in non-small cell lung cancer (NSCLC). The endogenous caspase-8 inhibitor, FLIP, is a critical regulator of cell death that is frequently overexpressed in NSCLC and is an established inhibitor of apoptotic cell death induced via the extrinsic death receptor pathway. Apoptosis induced by ionizing radiation (IR) has been considered to be mediated predominantly via the intrinsic apoptotic pathway; however,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
3
19
0
1
Order By: Relevance
“…Moreover, siRNA-mediated downregulation of FLIP [particularly FLIP(L)] significantly enhanced chemotherapy-induced cell death. Similar results were found with cisplatin in NSCLC models, docetaxel in prostate cancer models and more recently in combination with ionizing radiation in NSCLC [9]. Similarly, increased levels of FLIP(S) induced by AKT/mTOR/ S6K1 and the Ral effector protein (RalBP1) have been linked to inhibition of cisplatin and oxaliplatininduced apoptosis [93,127,[141][142][143][144][145].…”
Section: Flip As a Mediator Of Therapy Resistancesupporting
confidence: 73%
“…Moreover, siRNA-mediated downregulation of FLIP [particularly FLIP(L)] significantly enhanced chemotherapy-induced cell death. Similar results were found with cisplatin in NSCLC models, docetaxel in prostate cancer models and more recently in combination with ionizing radiation in NSCLC [9]. Similarly, increased levels of FLIP(S) induced by AKT/mTOR/ S6K1 and the Ral effector protein (RalBP1) have been linked to inhibition of cisplatin and oxaliplatininduced apoptosis [93,127,[141][142][143][144][145].…”
Section: Flip As a Mediator Of Therapy Resistancesupporting
confidence: 73%
“…FLIP is a major apoptosis-regulatory protein frequently overexpressed in solid and hematological cancers and is an important mediator of chemo-and radio-resistance as well as apoptosis induced by immune effector cells and therapeutic agonists [35][36][37][38] . For these reasons, high FLIP expression has been correlated with poor prognosis in a number of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been demonstrated that secretions by cells in the tumor microenvironment may enhance the radiation resistance of tumor cells (26,27), including recently studied exosomes (28). Regarding the relationship between NSCLC and radiation resistance, many studies have focused on identifying internal regulatory factors of these cells (29,30). In the present study, it was demonstrated that H460 cell-derived secretions could provide a favorable tumor microenvironment for protecting the cells against radiation effects, and that the mediating factors were not exosome-dependent.…”
Section: Discussionmentioning
confidence: 99%